Community Structure Of Mushroom Coral (Fungiidae) In Banggai Island , Central Sulawesi - Hermanto, Bambang; Souhoka, Jemmy (Jurnal Ilmiah PLATAX, 2015)
Mushroom coral is one of the component of hard coral family in ordo Scleratinia where this life was free living on substrate. Structure community of mushroom coral study in the waters of the Banggai Archipelago in Central Sulawesi province has not been done much. Observation on community structure of mushroom coral at Banggai Archipelago waters was conducted on July 2011. The purpose of this study  to determine the species composition, diversity, evenness, density and dominance species of musrhoom coral.The method used in this research is belt transects that made ​​ parallelly extended to the shoreline with the size of 100 x 3 m2. Mushroom coral species observation done visually by counting the number of species.  It was found 27 species belong to 10 genus of mushroom corals. The highest diversity index (H) was 1,19 at station 9 and the minimum was 0,95 at station 4.  The highest avenness index (j) was 0,69 at station 3 and the minimum was 0,44 at station 8.  The highest dominance index (D) was 0,14 at station 7 and minimum was 0,08 at station 6.  Identification results shows that there are 5 species of mushroom coral found in the 9 station, which is Fungia concinna, F. repanda, F. fungites, F. costulata and Herpolita limax. Keywords : community structure, mushroom coral, banggai archipelago, Central Sulawesi   ABSTRAK Karang jamur merupakan salah satu family karang batu yang masuk dalam ordo Scleractinia dimana hidupnya bebas pada substrat. Penelitian mengenai struktur komunitas karang jamur di perairan kepulauan Banggai propinsi Sulawesi Tengah belum banyak dilakukan. Pengamatan struktur komunitas karang jamur di perairan Kepulauan Banggai telah dilakukan pada bulan Juli 2011. Tujuan penelitian ini yaitu untuk melihat komposisi jenis, keanekaragaman jenis, kemerataan jenis, kepadatan dan dominansi jenis karang jamur.  Metode yang digunakan dalam penelitian ini yaitu transek sabuk yang dibuat memanjang garis pantai dengan luas transek 100 x 3m². Pengamatan jenis karang jamur dilakukan secara visual dengan menghitung jumlah tiap jenis.  Hasil analisis menunjukkan jumlah jenis karang jamur yang ditemukan sebanyak 27 jenis yang mewakili 10 marga.  Indeks keanekaragaman jenis (H) tertinggi dijumpai di stasiun 9 sebesar 1,19 dan terendah di stasiun 4 sebesar 0,95.  Indeks kemerataan jenis (j) tertinggi ditemukan di stasiun 3 sebesar 0,69 dan terendah di stasiun 8 sebesar 0,44.  Indeks dominansi jenis (D) tertinggi dijumpai di stasiun 7 sebesar 0,14 dan terendah di stasiun 6 sebesar 0,08.  Hasil identifikasi jenis menunjukkan ada 5 jenis karang jamur yang ditemukan di 9 stasiun yaitu Fungia concinna, F. repanda, F. fungites, F. costulata dan Herpolita limax. Kata kunci : Struktur komunitas, Karang jamur, Kepulauan Banggai